PATHOMORPHOLOGICAL CHANGES IN THE VESSELS OF THE HEART AND THE LUNGS IN PNEUMOCONIOSIS - Михайлова, Надежда Николаевна; Бондарев, Олег Иванович; Бугаева, Мария Сергеевна (Medicine in Kuzbass, 2017)
Subject – pathomorphological changes in the vessels of the heart and the lungs in pneumoconiosis. Objective. The study of the morphological changes in the wall of the vessels of the heart and the lungs in the dynamics of the development of the pneumoconiotic process. Methods. A histological and morphometric study of the autopsy material of the heart and lung vessels that was obtained in carrying out 60 forensic tests of the miners who had different length of the work was carried out. To study the early morphological changes in the vessels of the cardiac muscle and of the lungs that develop with prolonged exposure to a dusty factor an experiment was carried out on white laboratory male rats, which were exposed to inhalation of the coal-rock dust of the gas fatty type in a priming chamber. The total duration of the experiment was 12 weeks. Main results. In the conditions of the prolonged exposure to coal-rock dust on the body in the vessels of the heart and the lungs we observed the formation of similar pathological changes in the form of endotheliosis, hypertrophy of the medial layer, thickening of the wall, perivascular fibrosis. These disturbances began to be noted in the miners who had worked in underground conditions for more than 5 years and progressed with an increasing of the length of the work that led to the remodeling of the vessels of different diameters. Similar disorders of the structure of the vessels of the heart and of the lungs were formed during the experimental pneumoconiosis modeling. Morphological changes began to develop after 3 weeks of exposure to coal-rock dust and reached a maximum degree of expression by the 12th week of the experiment. Area of application. The results dictate the need to determine the early changes in the vessels of cardiac muscle and lungs for timely diagnosis and prevention of emerging disorders. Conclusions. The long-term exposure to coal-rock dust is a risk factor for the development of morphological disturbances in the vessels of the heart and lungs.